Separation membranes, separation membrane modules, filtration devices, and purified microbial or cell-derived products obtained using them.
Patent Information
- Application Number
- JP2026057162
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167634000006 
Figure 2026167634000001 
Figure 2026167634000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to separation membranes, separation membrane modules, filtration devices, and purified products of microorganisms or cell-derived substances purified using the same. [Background technology]
[0002] Biopharmaceuticals are being actively developed as effective medicines for diseases that were difficult to treat with conventional small-molecule drugs. Biopharmaceuticals are a general term for medicines that use substances produced from microorganisms or cells as active ingredients, and include protein drugs, vaccines, antibody drugs, gene therapy drugs, and extracellular vesicles. Many protein drugs and antibody drugs are already on the market. Furthermore, it is expected that the number of gene therapy drugs (viral vectors, etc.) and extracellular vesicles (especially small extracellular vesicles with a diameter of 40 nm to 150 nm) that will be sold as medicines will increase in the future, and technologies for efficiently purifying them are needed.
[0003] Biopharmaceuticals are generally sensitive to heat, making purification by distillation extremely difficult. Furthermore, due to their large molecular weight, purification by crystallization is also generally very difficult. For these reasons, membrane separation technology is considered a promising technique for purifying biopharmaceuticals.
[0004] In membrane separation, it is necessary to pass a liquid containing a high concentration of dissolved protein through a separation membrane and filter it. However, when a high-concentration protein solution comes into contact with the separation membrane, the protein adheres to the membrane. This can lead to a decrease in the recovery rate of biopharmaceuticals and a decrease in the permeability of the separation membrane, requiring filtration for extended periods, increasing filtration pressure, or necessitating membrane replacement due to clogging.
[0005] Various techniques for preventing high-concentration proteins from adhering to separation membranes have been studied in the fields of medical materials and biopharmaceutical manufacturing. For example, Patent Document 1 and Patent Document 2 disclose techniques for increasing the hydrophilicity of a separation membrane and suppressing protein adhesion to the separation membrane by adding polyvinylpyrrolidone, which is a hydrophilic polymer, to the separation membrane.
[0006] Furthermore, Patent Document 3 and Patent Document 4 also disclose a technique for immobilizing a compound having a monocarboxylic acid vinyl ester structure, which has a higher protein adhesion inhibitory ability than polyvinylpyrrolidone, in the dense layer on the inner surface of a hollow fiber membrane to suppress protein adhesion. [Prior Art Documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Examined Patent Publication No. 2-18695 [Patent Document 2] Japanese Unexamined Patent Publication No. 6-238139 [Patent Document 3] International Publication No. WO2009-123088 [Patent Document 4] International Publication No. WO2021-100804 [Summary of the Invention] [Problems to be Solved by the Invention]
[0008] However, the techniques for hydrophilizing the membrane surface disclosed in Patent Document 1 and Patent Document 2 have an insufficient protein adhesion inhibitory effect, and there is a problem that the recovery rate of biopharmaceuticals decreases.
[0009] Furthermore, in the techniques disclosed in Patent Document 3 and Patent Document 4, the protein adhesion inhibitory material is localized in the region of the dense layer on the inner surface of the hollow fiber membrane, so there is a problem that protein adhesion to the membrane thickness portion during filtration and protein adhesion to the outer surface of the hollow fiber membrane after filtration cannot be sufficiently suppressed.
[0010] The present invention aims to solve the above problems and provide a separation membrane that can improve the recovery rate of products from microorganisms or cells, particularly biopharmaceuticals, and that can maintain water permeability for a long period of time and continue filtering. [Means for solving the problem]
[0011] As a result of diligent research, the inventors have found that the above problem can be solved by setting the amount of the protein adhesion inhibiting material on both surfaces of the separation membrane and the distribution of the protein adhesion inhibiting material within the separation membrane to a predetermined range.
[0012] In other words, the present invention has the following configurations (1) to (18). (1) A separation membrane for purifying microbial or cell-derived substances, comprising a main polymer compound A, a hydrophilic polymer compound B, and a polymer compound C having an ester group, and having a dense layer, and satisfying the following conditions (A) to (C). (A) When the surfaces on both sides of the above-mentioned separation membrane are measured by X-ray photoelectron spectroscopy (XPS), the peak area derived from the ester group carbon atoms of polymer compound C among the total carbon-derived peak area is between 0.5 atomic% and 10.0 atomic%. (B) When the surfaces on both sides of the above-mentioned separation membrane are measured by X-ray photoelectron spectroscopy (XPS), the ratio of the atomic abundance of the surface on the side with a larger peak area derived from ester group carbon atoms to the atomic abundance of the surface on the side with a smaller peak area derived from ester group carbon atoms is 1.0 or greater and 2.2 or less. (C) In time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis of the cross-section in the film thickness direction of the above separation membrane, the average detection intensity of ions derived from the ester group of polymer compound C in the region 20 μm from the surface on the side closer to the dense layer is 1.1 times or more and 10.0 times or less than the average detection intensity in the region 20 μm from the surface on the side farther from the dense layer. (2) The separation membrane according to (1), wherein, in time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis of the cross-section in the direction of film thickness, the average detection intensity of ions derived from the ester group of polymer compound C is 0.01 times or more and 1.50 times or less than the average detection intensity of ions derived from polymer compound B in a region 20 μm from any surface. (3) The separation membrane according to (1) or (2), wherein the average pore size of the surface on the side closest to the dense layer is 0.04 μm or more and 2.00 μm or less. (4) The separation membrane according to (1) to (3), wherein, in a cross-section in the direction of film thickness, the porosity in the region from the surface on the side closest to the dense layer to a depth of 20 μm is 25% or more and 75% or less. (5) The separation membrane according to (1) to (4), wherein in a cross-section of the separation membrane in the direction of film thickness, the dense layer is located at a depth of 1 μm or more and 20 μm or less from the surface. (6) The separation membrane is a hollow fiber membrane, as described in (1) to (5). (7) The separation membrane according to (1) to (6), wherein the polymer compound A is a polysulfone polymer compound. (8) The separation membrane according to (1) to (7), wherein the polymer compound B is a polymer compound containing nitrogen atoms. (9) The separation membrane according to (1) to (8), wherein the polymer compound C is a polymer compound having a monocarboxylate vinyl ester unit as a repeating unit. (10) A separation membrane as described in (1) to (9), having a nitrogen content of 2.0 mg / g or more and 5.0 mg / g or less. (11) A separation membrane as described in (1) to (10), having a film thickness of 60 μm or more and 200 μm or less. (12) A separation membrane as described in (1) to (11), wherein the transmittance of particles with a particle size of 0.06 μm is 1% or more and 100% or less. (13) A separation membrane module containing the separation membranes described in (1) to (12). (14) The separation membrane module according to (13), wherein the water content in the separation membrane is 1 to 350% by mass. (15) The separation membrane module according to (14), wherein the water content in the separation membrane is 1 to 50% by mass. (16) A filtration apparatus having the separation membrane module and liquid transfer pump described in (13). (17) A purified product of microbial or cell-derived substances obtained by filtering the culture medium or culture supernatant of a microorganism or cell through the separation membrane module described in (13). (18) The purified product according to (17), wherein the product produced from the above microorganism or cell is a vector, an antibody, or an extracellular vesicle. [Effects of the Invention]
[0013] The present invention provides a separation membrane with minimal protein adhesion. Furthermore, when the separation membrane of the present invention is used for the purification of microbial or cell-derived substances, membrane clogging during filtration is reduced, and purified microbial or cell-derived products can be obtained with a high recovery rate. [Brief explanation of the drawing]
[0014] [Figure 1] This figure shows the results of the analysis of 3D SEM (scanning electron microscope) data obtained for a region of 10 μm from the outer surface of the hollow fiber membrane manufactured by the method of Example 1. [Modes for carrying out the invention]
[0015] The following describes in detail preferred embodiments of separation membranes, separation membrane modules, filtration devices, and purified products of microorganisms or cell-derived substances. However, the present invention is not limited to the following embodiments and can be implemented with various modifications depending on the purpose and application. <Separation membrane> The separation membrane of the present invention (hereinafter, membranes that do not contain all of polymer compounds A, B, and C may be referred to as "separation membrane precursors") is a separation membrane having a dense layer. Among separation membranes, the separation membrane of the present invention is preferably an asymmetric separation membrane because it can achieve both water permeability and separation performance. An "asymmetric separation membrane" is a membrane having a structure in which the pore size is smallest in the dense layer, and the pore size gradually increases from the dense layer toward the membrane surface. Among asymmetric separation membranes, it is preferable that the membrane has a gradient structure in the film thickness where the pore size decreases from one membrane surface toward the other membrane surface.
[0016] In this invention, the "dense layer" refers to the layer containing the smallest pore size when the cross-section of the membrane is observed with an electron microscope. If there are multiple layers with smaller pore sizes within the separation membrane, the layer with the smallest pore size is designated as the dense layer. The depth of the dense layer refers to the region where no pores with a pore size of 0.20 μm or larger exist when the cross-section of the separation membrane is observed using the method described in Example (5) Measurement of Dense Layer Depth. If there are abnormally large pores (void structures) within the dense layer that are clearly different from the surrounding areas, these abnormally large pores shall be excluded when determining the location and thickness of the dense layer.
[0017] Furthermore, the "coarse layer" refers to the layer portion other than the dense layer. Due to its asymmetric structure, it has regions with small pore sizes that contribute to separation and regions with large pore sizes that have low water permeability resistance, allowing it to exhibit separation performance while maintaining high water permeability.
[0018] When the separation membrane is in the form of a hollow fiber membrane, the inner surface may be a dense layer, or the outer surface may be a dense layer. However, since internal pressure filtration is often used in biopharmaceutical manufacturing processes, it is preferable that a coarse layer exists on the inner surface side and a dense layer exists near the outer surface.
[0019] The separation membrane of the present invention contains polymer compound A as its main component, which will be described later.
[0020] The separation membrane of the present invention is preferably in the shape of a hollow fiber membrane, from the viewpoint that a large membrane area can be obtained relative to the case size when it is filled into a separation membrane module case.
[0021] The film thickness of the separation membrane of the present invention is preferably 40 μm or more and 300 μm or less. From the viewpoint of separation membrane strength, the film thickness of the separation membrane is more preferably 60 μm or more, even more preferably 80 μm or more, even more preferably 100 μm or more, and particularly preferably 120 μm or more. On the other hand, since the film thickness portion becomes the resistance to the permeation of substances, the film thickness of the separation membrane is more preferably 270 μm or less, even more preferably 250 μm or less, even more preferably 220 μm or less, and particularly preferably 200 μm or less.
[0022] When the separation membrane of the present invention is a hollow fiber membrane, the inner diameter of the hollow fiber membrane is preferably 150 μm or more and 3000 μm or less. From the viewpoint of increasing a certain effective hollow fiber membrane area without increasing the number of hollow fiber membranes and from the viewpoint of reducing pressure loss during use, the inner diameter of the hollow fiber membrane is more preferably 160 μm or more, even more preferably 180 μm or more, even more preferably 190 μm or more, and particularly preferably 210 μm or more. On the other hand, the inner diameter of the hollow fiber membrane is more preferably 2600 μm or less, even more preferably 2300 μm or less, even more preferably 2000 μm or less, and particularly preferably 1600 μm or less.
[0023] One method for setting the inner diameter of the hollow fiber membrane within the above range is to adjust the amount of core liquid discharged during spinning.
[0024] One method for adjusting the film thickness of the separation membrane within the above range is to control the discharge rate of the film-forming solution during film formation. Furthermore, in the case of hollow fiber membrane formation, the film thickness can also be adjusted by the design of the nozzle.
[0025] In the separation membrane of the present invention, the average pore size of the surface on the side closest to the dense layer is preferably 0.04 μm or more and 2.00 μm or less. Substances used as biopharmaceuticals are generally several to tens of nanometers or larger in size, and in order for the separation membrane to exhibit high permeability to these substances, the average pore size of the surface on the side closest to the dense layer is preferably 0.04 μm or more, more preferably 0.10 μm or more, even more preferably 0.20 μm or more, even more preferably 0.30 μm or more, and particularly preferably 0.50 μm or more, in order to allow for the permeability of larger substances as needed. On the other hand, the average pore size of the surface on the side closest to the dense layer of the separation membrane is more preferably 1.80 μm or less, even more preferably 1.50 μm or less, even more preferably 1.20 μm or less, and particularly preferably 1.00 μm or less.
[0026] Methods for setting the average pore diameter of the surface on the side of the separation membrane closest to the dense layer to the above range include, for example, in the case of a hollow fiber membrane, adjusting the concentration of poor solvent vapor relative to the main components constituting the hollow fiber membrane in the dry section during film formation described later, or adjusting the spindle temperature during spinning. When the separation membrane of the present invention is a hollow fiber membrane, from the viewpoint of ease of film formation, it is more preferable that the average pore diameter of the outer surface of the hollow fiber membrane is smaller than the average pore diameter of the inner surface of the hollow fiber membrane.
[0027] The separation membrane of the present invention preferably has a dense layer. By having a dense layer, there are dense regions (dense layer) that contribute to the separation of substances to be removed and coarse regions (coarse layer) with large pore sizes and low water permeability resistance, making it easier to achieve both separation performance and water permeability.
[0028] The position of the dense layer within the separation membrane is arbitrary, and it may be on the side closest to either surface. The dense layer may be continuous with any surface, but in the separation membrane of the present invention, it is preferable that the dense layer is located at a depth of 1 μm to 20 μm from any surface in the cross-section in the film thickness direction of the separation membrane.
[0029] Here, the depth of the dense layer refers to the distance from the edge of the dense layer to the nearest surface. It is preferable for the dense layer to be located at a certain depth, as this reduces the likelihood of damage to the dense layer due to external friction and shear stress during filtration.
[0030] In the separation membrane of the present invention, the thickness of the dense layer in the cross-section of the separation membrane is preferably 1.0 μm or more and 20.0 μm or less. Having the dense layer thickness within this range makes it possible to achieve both high permeability and high separation function, and it is possible to suppress an increase in filtration pressure even when the processing volume of the liquid to be treated is increased. From the viewpoint of reducing the permeation resistance of substances, the thickness of the dense layer is preferably 14.0 μm or less, more preferably 12.0 μm or less, even more preferably 11.0 μm or less, and particularly preferably 10.0 μm or less. On the other hand, since the dense layer is a layer that has the effect of improving the separation function of the separation membrane, it is preferable to have a certain thickness or more. That is, the thickness of the dense layer is more preferably 1.5 μm or more, even more preferably 2.0 μm or more, and particularly preferably 2.5 μm or more.
[0031] In the separation membrane of the present invention, the average pore size of the surface on the side furthest from the dense layer is preferably 0.50 μm or more and 30.00 μm or less. By setting the average pore size of the surface on the side furthest from the dense layer within the above range, it is possible to prevent microorganisms and cells from entering the interior of the separation membrane when they are present in the culture medium. By preventing the entry of microorganisms and cells, the membrane is less likely to clog, and the separation membrane can be used for a longer period of time.
[0032] Because microorganisms and cells are easily deformed by external forces, the average pore size on the surface furthest from the dense layer is more preferably 25.00 μm or less, even more preferably 20.00 μm or less, and even more preferably 15.00 μm or less. On the other hand, increasing the pore size improves permeability and productivity, so it is more preferably 0.60 μm or more, and even more preferably 0.70 μm or more.
[0033] Methods for setting the average pore size of the surface on the far side of the dense layer of the separation membrane to the above range include, for example, in the case of a hollow fiber membrane, adjusting the concentration of the main component constituting the hollow fiber membrane (e.g., polysulfone) in the film-forming stock solution during film formation, or adjusting the coagulation value of the injection liquid (core liquid) for forming the hollow portion. The coagulation value is defined as the amount of injection liquid added when the system becomes cloudy after adding small amounts of injection liquid to 50 g of a solution in which the main component constituting the hollow fiber membrane is dissolved in a solvent to a concentration of 1% by mass.
[0034] In the separation membrane of the present invention, from the viewpoint of reducing permeation resistance, obtaining high water permeability, and obtaining strength of the separation membrane, it is preferable that the porosity in the region from the surface on the side closest to the dense layer to a depth of 20 μm is 25% or more and 75% or less. From the viewpoint of reducing permeation resistance, it is more preferable that the porosity in the said region is 30% or more. Furthermore, from the viewpoint of obtaining sufficient strength, it is more preferable that the porosity in the said region is 70% or less.
[0035] The porosity is obtained by calculating the area of the film structure and the void portion in a scanning electron microscope (SEM) image of a cross-section of the film from the surface near the dense layer to a depth of 20 μm, and then calculating the proportion of the void portion.
[0036] The depth from the surface closest to the dense layer refers to the distance along the perpendicular to the tangent line drawn to the surface closest to the dense layer when the separation membrane is a flat membrane, and the distance from the intersection of the line drawn from the central axis of the hollow fiber membrane to the surface closest to the dense layer, through the interior of the membrane, when the separation membrane is a hollow fiber membrane when the separation membrane is a hollow fiber membrane. If the cross-section of the hollow fiber membrane is not a perfect circle, the central axis of the hollow fiber membrane refers to the center when the cross-section is approximated as a circle.
[0037] In calculating the area of the membrane structure portion and the void portion, the SEM image is binarized in the same manner as in Example (6) "Average pore diameter on the surface of the separation membrane," and the area of the membrane structure portion and the pore portion are calculated using image processing software (ImageJ (version 1.52), developed by the National Institutes of Health, USA).
[0038] Even if the porosity is high on the side closest to the dense layer, independent pores that are not connected do not contribute to water permeability or permeability, so it is preferable to have more connected pores. The number of connected pores can be determined by performing 3D SEM observation and image analysis on the region of the separation membrane that includes the dense layer. 3D SEM observation is obtained by slicing the sample at a pitch of several nanometers to tens of nanometers and observing it with SEM. PNM (Pore Network Model) analysis is one of the image analysis methods for the obtained 3D SEM data.
[0039] As an example, Figure 1 shows the results of an analysis of 3D SEM data obtained for a region of 10 μm from the outer surface of a hollow fiber membrane manufactured by the method of Example 1 described later. In Figure 1, numerous interconnected pores (called "throats") exist inside surface 1 on the side closer to the dense layer on the outer surface of the hollow fiber membrane, and it is thought that these numerous interconnected structures, represented by Throats 2, contribute to the high water permeability and permeability of the separation membrane of the present invention. In other words, when 3D observation and PNM analysis were performed on the separation membrane of the present invention up to a depth of 10 μm from the surface on the side closer to the dense layer, the Throat density was 45 pores / μm 3 More than 80 lines / μm 3 The following is preferable:
[0040] The separation membrane of the present invention preferably has a transmittance of 1% or more and 100% or less for particles with a particle size of 0.06 μm. This is because it is preferable that the separation membrane of the present invention allows biopharmaceuticals, more specifically viral vectors, antibodies, or extracellular vesicles, to pass through with a sufficiently productive transmittance. In this specification, polystyrene latex particles are used for measuring particle transmittance as described in "(4) Measurement of Particle Transmittance" below.
[0041] To further increase productivity and enable application to the purification of a wider variety of biopharmaceuticals, the transmittance of particles with a particle size of 0.06 μm is more preferably 2% or more, even more preferably 5% or more, and even more preferably 10% or more. Furthermore, considering cases where the liquid to be treated is a high-density cell culture medium or culture supernatant, the transmittance of particles with a particle size of 0.06 μm is particularly preferably 20% or more, and most preferably 35% or more.
[0042] When the separation membrane of the present invention is a hollow fiber membrane, it is preferable that it has a three-dimensional network structure. Here, a three-dimensional network structure refers to a structure in which solid components are spread out in a three-dimensional network pattern. The three-dimensional network structure has pores separated by the solid components that form the network.
[0043] <Main component polymer compound A> The separation membrane of the present invention contains polymer compound A as its main component, and an amorphous polymer is preferably used as polymer compound A. An amorphous polymer is a polymer that does not crystallize and does not exhibit an exothermic peak due to crystallization when measured with a differential scanning calorimeter.
[0044] Because amorphous polymers readily undergo structural deformation, structural control in the film thickness direction is easily achieved. Separation membranes made from amorphous polymers are obtained by inducing phase separation in a film-forming stock solution, prepared by dissolving the amorphous polymer in a solvent, using heat or a poor solvent, and then removing the solvent components. The amorphous polymer dissolved in the solvent has high mobility and aggregates during phase separation, increasing its concentration and forming a dense structure. By changing the rate of phase separation in the film thickness direction, it is possible to obtain membranes with an asymmetric structure in which the pore size differs with respect to the film thickness direction.
[0045] Examples of amorphous polymers used as materials for separation membranes include acrylic polymers, vinyl acetate polymers, and polysulfone polymers. Among these, polysulfone polymers are preferred because their pore size is easily controllable and they have high strength. In other words, the separation membrane of the present invention is more preferably a separation membrane in which polymer compound A is a polysulfone polymer compound, with polysulfone polymer compound being the main component.
[0046] In this invention, the main component refers to the component that is most abundant by mass in the separation membrane.
[0047] In this invention, the polysulfone polymer has an aromatic ring, a sulfonyl group, and an ether group in its main chain. For example, the polysulfone polymers shown in the following structural formulas (I) and (II) are preferably used, but the invention is not limited to these. For example, molecules or polymers may be graft polymerized, such as by introducing a sulfonic acid group into a part of the aromatic ring. In the formula, n is an integer such as 50 to 80.
[0048] [ka] [ka]
[0049] Specific examples of polysulfones include “Udel”® polysulfone P-1700 and P-3500 (manufactured by SOLVAY), and “Ultrasone”® S3010 and S6010 (manufactured by BASF). Furthermore, while polymers consisting only of the repeating units shown in structural formulas (I) and (II) above are preferred as polysulfones used in the present invention, copolymers with other monomers are also acceptable as long as they do not hinder the effects of the present invention. Although not particularly limited, it is preferable that the other copolymerized monomers be 10% by mass or less.
[0050] <Hydrophilic polymer compound B> The separation membrane of the present invention contains hydrophilic polymer compound B. Possible methods for incorporating the hydrophilic polymer into the separation membrane include encapsulation in a closed vesicle structure, attachment (physical adsorption), or chemical immobilization, but it is preferable that the polymer is supported by attachment or chemical immobilization. By supporting the hydrophilic polymer on the surface of the separation membrane, it is possible to suppress the adsorption of proteins in the liquid to be treated, such as culture medium, and clogging due to adsorption, thereby improving the permeability of the target substance and suppressing the aggregation of substances in the liquid to be treated.
[0051] Here, hydrophilic polymers refer to water-soluble polymers or polymers that, even if not water-soluble, interact with water molecules through electrostatic interactions or hydrogen bonding. Here, water-soluble polymers refer to polymers that dissolve in pure water at 25°C at a concentration of 1000 ppm (0.1 g / mL) or more. Specific examples of water-soluble polymers include, for example, polyalkylene glycols such as polyethylene glycol or polypropylene glycol, nonionic hydrophilic polymers such as polyvinyl alcohol or polyvinylpyrrolidone, or ionic hydrophilic polymers such as dextran sulfate, polyacrylic acid, polyethyleneimine, and polyallylamine.
[0052] Examples of hydrophilic polymers that interact with water molecules through electrostatic interactions or hydrogen bonding, even if they are not water-soluble, include nonionic hydrophilic polymers such as polyvinyl acetate, polyvinyl caprolactam, hydroxyethyl methacrylate, or methyl methacrylate.
[0053] The hydrophilic polymer described above may be copolymerized with other monomers.
[0054] In the separation membrane of the present invention, when a hydrophilic polymer is contained, the content of the hydrophilic polymer is preferably 5.0% by mass or more and 15.0% by mass or less. From the viewpoint that the inclusion of a hydrophilic polymer in the separation membrane improves the wettability of the separation membrane and improves water permeability and permeability, the content of the hydrophilic polymer is more preferably 7.0% by mass or more, even more preferably 9.0% by mass or more, even more preferably 11.0% by mass or more, and particularly preferably 12.0% by mass or more. On the other hand, the lower the content of the hydrophilic polymer in the separation membrane, the more the elution during use is suppressed and the less the change in the performance of the separation membrane can be suppressed, so the content of the hydrophilic polymer is more preferably 14.5% by mass or less, and particularly preferably 14.0% by mass or less.
[0055] The content of hydrophilic polymers in the separation membrane requires selecting a measurement method depending on the type of polymer, but it can be determined by combining elemental analysis and nuclear magnetic resonance (NMR). From the viewpoint of exhibiting high hydrophilicity, the polymer compound B contained in the separation membrane of the present invention and the polymer compound C having an ester group, described in the next section, are preferably polymer compounds containing nitrogen atoms. In the separation membrane of the present invention, from the viewpoint of controlling the hydrophilicity of the separation membrane, it is preferable to control the total nitrogen content of the separation membrane derived from hydrophilic polymer compound B and the separation membrane derived from polymer compound C having an ester group, described in the next section. The nitrogen content in the separation membrane of the present invention shall be measured according to Example "(9) Measurement of Nitrogen Content in Separation Membrane". Furthermore, the nitrogen content in the separation membrane is preferably 2.0 mg / g or more and 5.0 mg / g or less.
[0056] The hydrophilic polymer can be appropriately selected depending on the material of the hollow fiber membrane and its affinity to the solvent. There are no particular limitations, but in the case of polysulfone polymers, polyvinylpyrrolidone is preferably used due to its high compatibility.
[0057] By adding hydrophilic polymers to the film-forming solution, the hydrophilic polymers are incorporated into the hollow fiber membrane, improving wettability and increasing water permeability. Furthermore, it becomes possible to adjust the viscosity of the film-forming solution, i.e., the pore size.
[0058] <Polymer compound C containing an ester group> The separation membrane of the present invention contains a polymer compound C having an ester group.
[0059] Polymer compound C, which contains an ester group, is a polymer compound that has a protein adhesion inhibitory effect. Among compounds that have a protein adhesion inhibitory effect, polymer compounds containing an ester group are preferred from the viewpoint of chemical stability and minimal impact on pH, and because they are polymers, they are easy to support on separation membranes.
[0060] Furthermore, among polymer compounds C containing ester groups, polymers containing monocarboxylate vinyl ester units are particularly preferred. That is, polymer compounds C that have monocarboxylate vinyl ester units as repeating units are preferred.
[0061] With respect to polymers containing monocarboxylate vinyl ester units, a monocarboxylic acid refers to a compound consisting of one carboxyl group and a hydrocarbon group bonded to the carbon atom of the carboxyl group, i.e., a compound represented as "R-COOH" (where R is the hydrocarbon group). The hydrocarbon group R may be either an aliphatic hydrocarbon group or an aromatic hydrocarbon group, but from the viewpoint of ease of synthesis, an aliphatic hydrocarbon group is preferred, and a saturated aliphatic hydrocarbon group is more preferred.
[0062] Examples of saturated aliphatic hydrocarbon groups include those with a linear structure such as ethyl group, n-propyl group, n-butyl group, n-pentyl group, or n-hexyl group; those with a branched structure such as isopropyl group or tert-butyl group; or those with a cyclic structure such as cyclopropyl group or cyclobutyl group. Furthermore, the aliphatic chain may contain ether bonds or ester bonds. Among these, from the viewpoint of the cost of producing carboxylic acids, saturated aliphatic hydrocarbon groups are preferably linear or branched, and more preferably linear.
[0063] Examples of monocarboxylic acids in which the hydrocarbon group R is an aromatic hydrocarbon group include benzoic acid and its derivatives. Examples of monocarboxylic acids in which the hydrocarbon group R is a saturated aliphatic hydrocarbon group include acetic acid, propanoic acid, or butyric acid.
[0064] Furthermore, the hydrocarbon group R may have at least some of its hydrogen atoms optionally substituted. In this case, the substituent is preferably a nonpolar group or a cationic functional group, as this reduces the likelihood of protein denaturation due to contact and subsequent protein adsorption to the hollow fiber membrane surface.
[0065] A low number of carbon atoms in the hydrocarbon group R is preferable for reducing the hydrophobicity of the monocarboxylic acid, thereby minimizing hydrophobic interactions with proteins and preventing adhesion. Therefore, when R is an aliphatic hydrocarbon group or an aromatic hydrocarbon group, the number of carbon atoms is preferably 20 or less, more preferably 9 or less, and even more preferably 5 or less. On the other hand, when R is an aliphatic hydrocarbon group or an aromatic hydrocarbon group, the number of carbon atoms is 1 or more, but from the viewpoint of improving the mobility of the monocarboxylic acid and further suppressing protein adhesion, 2 or more is preferred. When R is a saturated aliphatic hydrocarbon group, the compound with 1 carbon atom is acetic acid, and the compound with 2 carbon atoms is propanoic acid.
[0066] Furthermore, in this specification, "repeating unit" refers to a repeating unit in a homopolymer or copolymer obtained by polymerizing monomers, and "vinyl carboxylate unit" means a repeating unit obtained by polymerizing vinyl carboxylate monomers, i.e., a repeating unit represented as "-CH(OCO-R)-CH2-" (where R is a hydrocarbon group). R is the same as described above for monocarboxylic acids, and preferred examples are also the same as above.
[0067] Furthermore, from the viewpoint of balancing hydrophilicity and hydrophobicity, the "vinyl carboxylate unit" is preferably a "vinyl monocarboxylate unit" obtained by polymerizing a vinyl monocarboxylate monomer.
[0068] Specific examples of monocarboxylate vinyl ester units in which the hydrocarbon group R is saturated aliphatic include vinyl propanoate, vinyl pivalate, vinyl decanoate, and vinyl methoxyacetate. Since it is preferable that the hydrophobicity is not too strong, vinyl acetate (R:CH3), vinyl propanoate (R:CH2CH3), vinyl butyrate (R:CH2CH2CH3), vinyl pentanoate (R:CH2CH2CH2CH3), vinyl pivalate (R:C(CH3)3), and vinyl hexanoate (R:CH2CH2CH2CH2CH3) are preferred examples. Specific examples of monocarboxylate vinyl ester units in which R is aromatic include vinyl benzoate and its substituted products.
[0069] The surface amount and distribution of polymer compound C supported on the separation membrane can be determined by combining time-of-flight secondary ion mass spectrometry (TOF-SIMS) and X-ray photoelectron spectroscopy (XPS) to measure the ion signal intensity derived from the ester group. This will be discussed later.
[0070] The weight-average molecular weight of polymer compound C is preferably 1,000 or more, and more preferably 5,000 or more, from the viewpoint of sufficiently suppressing the adhesion of proteins and other substances and allowing sufficient permeability of the target substance. On the other hand, from the viewpoint of introduction efficiency into the separation membrane, the weight-average molecular weight of polymer compound C is preferably 1,000,000 or less, more preferably 500,000 or less, and even more preferably 100,000 or less. The weight-average molecular weight of polymer compound C can be measured by gel permeation chromatography (GPC).
[0071] In particular, when supporting polymer compound C across the entire separation membrane, it is preferable to use a weight-average molecular weight that is smaller than the pore size of the separation membrane and easily permeates through it.
[0072] The polymer compound C, particularly the polymer compound containing monocarboxylate vinyl ester units, is preferably a copolymer (hereinafter sometimes simply referred to as "polymer") consisting of hydrophilic units and hydrophobic units, and more preferably the hydrophobic units contain monocarboxylate vinyl ester units. While polyethylene glycol and polyvinyl alcohol are known compounds other than polymer compound C contained in the separation membrane of the present invention that have a protein adhesion inhibitory effect, coating the separation membrane surface with these hydrophilic polymers may result in insufficient inhibition of protein adhesion. This is thought to be because excessive hydrophilicity of the separation membrane surface destabilizes the protein structure, making it difficult to adequately inhibit protein adhesion.
[0073] When the state of the water adsorbed by the protein and the state of the water adsorbed around the polymer are similar, the protein structure is not destabilized, and it is thought that the adhesion of the protein to the separation membrane surface can be suppressed. Copolymers consisting of hydrophilic and hydrophobic units allow for control of the state of the water adsorbed around the polymer by selecting the hydrophilic and hydrophobic groups used and the copolymerization ratio, and it is thought that the effect of suppressing protein adhesion can be further improved. Here, a hydrophilic unit refers to a polymer of the monomer constituting the unit with a weight-average molecular weight of 10,000 to 1,000,000 that is soluble in water. "Soluble" means that the solubility in 100g of water at 20°C is greater than 0.1g.
[0074] As monomers constituting the hydrophilic unit, monomers with a solubility of 10 g or more are more preferred. Examples of such monomers include vinyl alcohol monomers, acryloylmorpholine monomers, vinylpyridine monomers, vinylimidazole monomers, vinylpyrrolidone monomers, and the like. Two or more of these may be used.
[0075] Compared to monomers having carboxyl groups and sulfonic acid groups, monomers having amide bonds, ether bonds, and ester bonds are preferred as suitable monomers for constituting hydrophilic units because they are not excessively hydrophilic and are easier to balance with hydrophobic monomers. Among these, vinylacetamide monomers, vinylpyrrolidone monomers, and vinylcaprolactam monomers having amide bonds are particularly preferred. Of these, vinylpyrrolidone monomers are even more preferred because the toxicity of the polymer is low. Therefore, a preferred embodiment of the present invention is in which polymer compound C further contains vinylpyrrolidone units as hydrophilic units.
[0076] The monomers that constitute the hydrophobic unit include at least vinyl monocarboxylate esters, but other examples include acrylic acid esters, methacrylic acid esters, and vinyl-ε-caprolactam.
[0077] From the viewpoint of further suppressing protein adhesion, the mole fraction of hydrophobic units in the copolymer consisting of hydrophilic and hydrophobic units is preferably 10% or more and 90% or less, more preferably 20% or more and 80% or less, and even more preferably 30% or more and 70% or less. In this case, the hydrophobic units may consist only of monocarboxylate vinyl ester units, or other hydrophobic units may be included. By setting the mole fraction of hydrophobic units to 90% or less, the increase in the overall hydrophobicity of the copolymer can be suppressed, and protein adhesion can be further suppressed. On the other hand, by setting the mole fraction of hydrophobic units to 10% or more, the increase in the overall hydrophilicity of the copolymer can be suppressed, thereby avoiding structural instability and denaturation of proteins, and consequently further suppressing adhesion.
[0078] The above mole fraction can be calculated, for example, by performing nuclear magnetic resonance (NMR) measurements and determining the peak area. If it is not possible to calculate the above mole fraction by NMR measurement due to reasons such as overlapping peaks, the above mole fraction may be calculated by elemental analysis.
[0079] As the polymer compound C, a copolymer consisting of monocarboxylate vinyl ester units and vinylpyrrolidone units is particularly preferred. In this case, the molar ratio of vinylpyrrolidone units to monocarboxylate vinyl ester units is preferably 30:70 to 90:10, more preferably 40:60 to 80:20, and even more preferably 50:50 to 70:30.
[0080] Examples of repeating unit arrangements in the above copolymer include block copolymers, alternating copolymers, and random copolymers. Of these, alternating copolymers or random copolymers are preferred because they have a small distribution of hydrophilicity and hydrophobicity throughout the copolymer. Among these, random copolymers are more preferred because they are easy to synthesize.
[0081] Although not essential, it is preferable that polymer compound C is immobilized on the separation membrane by chemical bonding to avoid the elution of polymer compound C from the separation membrane during filtration.
[0082] Methods for supporting polymer compound C on a separation membrane include, for example, adding polymer compound C to the stock solution during film formation, or to the core solution if the separation membrane is a hollow fiber membrane, or contacting the surface with a polymer compound C solution after film formation. Among these, contacting the surface with a polymer compound C solution after film formation is preferred because it does not affect the film formation conditions. Methods for contacting the surface with a polymer compound C solution after film formation include immersing the separation membrane in the polymer compound C solution, passing the solution through the membrane, or spraying it with a sprayer. Among these, passing the polymer compound C solution through the separation membrane is preferred because it makes it possible to impart polymer compound C to the inside of the separation membrane.
[0083] When passing polymer compound C solution through a separation membrane, from the viewpoint of more efficiently introducing polymer compound C, the concentration of polymer compound C in the polymer compound C solution is preferably 10 ppm or more, more preferably 100 ppm or more, and even more preferably 300 ppm or more. On the other hand, from the viewpoint of suppressing elution from the module, the concentration of polymer compound C in the above solution is preferably 100,000 ppm or less, and more preferably 10,000 ppm or less.
[0084] Water is preferred as the solvent used to prepare the polymer compound C solution. However, if the required concentration cannot be dissolved in water, polymer compound C may be dissolved in an organic solvent that does not dissolve the separation membrane, or in a mixed solvent of an organic solvent that is compatible with water and does not dissolve the separation membrane, and water. Examples of organic solvents that can be used as the above organic solvent or mixed solvent include, but are not limited to, alcohol-based solvents such as methanol, ethanol, or propanol.
[0085] The direction in which the polymer compound C solution is passed through the separation membrane can be either from the dense layer side to the coarse layer side or from the coarse layer side to the dense layer side. However, from the viewpoint of efficiently imparting polymer compound C to the interior of the separation membrane, it is preferable to pass the solution from the coarse layer side to the dense layer side.
[0086] Furthermore, as mentioned above, it is preferable that the polymer compound C is immobilized on the separation membrane by chemical bonding. The method of immobilization by chemical bonding is not particularly limited, but examples include a method of graft polymerization of the polymer compound C by irradiating it with radiation after contact, and a method of introducing reactive groups such as amino groups or carboxyl groups on the surface of the separation membrane to be immobilized, and bonding the polymer compound C to the reactive groups by condensation.
[0087] <Cross-sectional TOF-SIMS analysis> In the separation membrane of the present invention, time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis of the cross-section in the film thickness direction of the separation membrane shows that the average detection intensity of ions derived from the ester group of polymer compound C in the region 20 μm from the surface on the side closer to the dense layer is 1.1 times or more and 10.0 times or less than the average detection intensity in the region 20 μm from the surface on the side farther from the dense layer.
[0088] TOF-SIMS analysis of a cross-section of the separation membrane allows for the detection of ions derived from ester groups. The origin of the ions can be determined by the mass (m / z) of the detected ions.
[0089] In TOF-SIMS measurements, pulsed ions (primary ions) are irradiated onto the surface of a sample placed in an ultra-high vacuum. The ions emitted from the sample surface (secondary ions) gain a constant kinetic energy and are guided to a time-of-flight mass spectrometer. Each secondary ion, accelerated by the same energy, passes through the analyzer at a speed corresponding to its mass. However, since the distance to the detector is constant, the time it takes to reach it (time of flight) is a function of mass. By precisely measuring the distribution of this time of flight, the mass distribution of the secondary ions, i.e., the mass spectrum, can be obtained.
[0090] For example, Bi as a primary ion species 3++ When detecting secondary positive ions using this method, the peak at m / z = 43.01 is C2H3O + This corresponds to acetic acid (aliphatic chain carbon number: 1). Also, the peak at m / z = 57.03 is C3H5O +, that is, corresponds to propanoic acid (aliphatic chain carbon number: 2).
[0091] The measurement conditions for ion signals by the TOF-SIMS apparatus are as follows. The measurement area is 120 μm × 150 μm, the primary ion acceleration voltage is 30 kV, and the pulse width is 117.6 ns. The detection depth in this analysis method is several nm or less. At this time, if the ion signal intensity derived from the ester group relative to the total secondary ion intensity is 0.1% or less, it is judged as noise, and it is assumed that no ester group-derived ions are present.
[0092] To cite more specific detected ion species, those derived from the chemical structure of polymer compound C suitably used in the separation membrane of the present invention, C3H5O + Ions are preferably detected. That is, the detected intensity of ions derived from the ester group carbon of polymer compound C is C3H5O + detection intensity, and the detected intensity of ions derived from polymer compound B is C6H 10 NO + , C8H 12 NO + , C 11 H 15 N2O2 + It is preferably the total detection intensity of the ions.
[0093] In the separation membrane of the present invention, from the viewpoint of exhibiting the wettability of the separation membrane, exhibiting high water permeability and permeability, and exerting the effect of suppressing the adhesion of proteins and the like, there is a preferable existence balance between polymer compound B and polymer compound C in the separation membrane. That is, in time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis of the cross-section in the film thickness direction, the average detected intensity of ester group-derived ions of polymer compound C in the region of 20 μm from any of the surfaces is preferably 0.01 times or more and 1.50 times or less of the average detected intensity of ions derived from polymer compound B.
[0094] <Surface XPS Measurement> The separation membrane of the present invention is used for the purification of biopharmaceuticals, and the target substance in the liquid to be processed passes through the inside of the separation membrane and exits to the filtration side. Furthermore, it remains present in a high concentration state on the filtration side. For these reasons, from the viewpoint of suppressing adsorption to the separation membrane during and after filtration, it is preferable that the polymer compound C is present throughout the entire separation membrane and on both surfaces.
[0095] In other words, when the surfaces on both sides of the separation membrane of the present invention are measured by X-ray photoelectron spectroscopy (XPS), it is preferable that the peak area derived from the ester group carbon atoms of polymer compound C is 0.5 atomic% or more and 10.0 atomic% or less of the total carbon-derived peak area, and that the ratio of the atomic abundance of the surface with a larger peak area derived from ester group carbon atoms to the atomic abundance of the surface with a smaller peak area derived from ester group carbon atoms is 1.0 or more and 2.2 or less.
[0096] XPS analysis revealed a peak originating from the ester group (COO) of the carbon, which is CH x Since the main peak of CC (around 285 eV) appears at +4.0 to 4.2 eV, it can be seen that the carboxylic acid is forming an ester bond. The XPS measurement angle used is 45°. The peak of the carbon originating from the ester group (COO) is C 1s This can be determined by splitting the main peaks originating from CH and CC into peaks appearing at +4.0 to 4.2 eV.
[0097] More specifically, C 1s The peak is mainly CH x CS, CC and C=C-derived components, mainly CO and CN-derived components, π-π *It consists of five components: components derived from satellites, components derived from C=O, and components derived from COO. By performing peak splitting on these five components and calculating the ratio of the peak area derived from ester groups to the total peak area derived from carbon, the amount of carbon (atomic %) derived from ester groups can be determined. In this case, if the ratio of the peak area derived from ester groups to the total peak area derived from carbon is 0.4% or less, it is judged as noise and it is assumed that no ester groups exist.
[0098] <Method for manufacturing separation membranes> One method for producing the separation membrane of the present invention, particularly a hollow fiber membrane, is to flow an injection liquid (core liquid) or injection gas from the inner circular tube of a double-walled nozzle and discharge the film-forming stock solution from the outer slit. In this process, the structure of the inner surface of the hollow fiber membrane can be controlled by changing the concentration and temperature of the poor solvent in the core liquid or by adding additives. On the other hand, the structure of the outer surface can be controlled by the atmospheric conditions of the dry section from the nozzle to the solidification bath and by the composition of the solidification bath. Since it is easier to control the structure of the inner surface of the hollow fiber membrane compared to the outer surface, it is preferable to use a hollow fiber membrane with an asymmetric structure where the pore diameter on the inner surface is large.
[0099] An example of a method for producing a hollow fiber membrane mainly composed of the polysulfone polymer described above is shown below. A phase separation method is preferred for forming the hollow fiber membrane. As a phase separation method, a method that induces phase separation with a poor solvent (non-solvent-induced separation method, NIPS) or a method that induces phase separation by cooling a high-temperature film-forming stock solution using a relatively low-solubility solvent (thermal-induced phase separation method, TIPS) can be used, but among these, film formation by inducing phase separation with a poor solvent is particularly preferred.
[0100] For example, one film-forming process involves using an orifice-type double-cylinder nozzle to simultaneously discharge a film-forming stock solution containing a polysulfone polymer from the outer cylinder and a core solution from the inner cylinder, passing them through a dry section, immersing them in a coagulation bath containing a coagulation solution to coagulate, and then washing them with hot water.
[0101] The concentration of polysulfone polymer in the above film-forming stock solution is preferably 10 to 25% by mass, and more preferably 10 to 20% by mass. The concentration of polysulfone polymer greatly affects the porosity on the surface of the hollow fiber membrane. When the concentration of polysulfone polymer is 25% by mass or less, the cohesive force between polysulfone polymers weakens during the film-forming process, making it difficult for the pressure to rise during the film-forming process and making it easier to improve the porosity on the surface of the separation membrane. On the other hand, when the concentration of polysulfone polymer is 10% by mass or more, although the porosity is lower, the strength of the hollow fiber membrane improves, making it less likely for the fibers to break.
[0102] Using hydrophilic polymers with relatively low molecular weight (weight-average molecular weight of 1,000 to 200,000) enhances pore formation, improves the porosity, and enhances the water permeability of hollow fiber membranes, although the pore size becomes relatively small. On the other hand, when using hydrophilic polymers with relatively high weight-average molecular weight (weight-average molecular weight of 200,000 to 1,200,000), the molecular chains are longer and the interaction with polysulfone polymers is greater, so they tend to remain in the hollow fiber membrane and contribute to improving the hydrophilicity of the hollow fiber membrane. However, the pore size also becomes relatively large.
[0103] The hydrophilic polymer added to the film-forming stock solution may be used alone, mixed with two or more other types, or blended with hydrophilic polymers having different weight-average molecular weights.
[0104] When preparing the film-forming stock solution, dissolving it at a high temperature of 30°C or higher is preferable to improve solubility. On the other hand, dissolving it at 120°C or lower can suppress the denaturation of polymers due to heat and compositional changes due to solvent evaporation. Therefore, the dissolution temperature is preferably between 30°C and 120°C. However, these optimal ranges may vary depending on the type of polymer and additive used.
[0105] In the above film-forming process, the core solution refers to the liquid present in the hollow portion formed by the hollow fiber membrane during the manufacturing process, and is a solution containing a good solvent for polysulfone polymers. Examples include N,N-dimethylacetamide, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, glycerin, or mixtures thereof. To increase spinning stability, polyvinylpyrrolidone, a copolymer containing vinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, polyacrylic acid, or polyethyleneimine may be added to the core solution.
[0106] The composition of the core solution significantly affects the porosity, average pore size, pore shape, and hydrophilic polymer content on the hollow fiber membrane surface. Increasing the concentration of good solvents in the core solution can alleviate aggregation of polysulfone polymers, resulting in a hollow fiber membrane with a high porosity and large pore size on the membrane surface. Adding hydrophilic polymers to the core solution not only localizes the hydrophilic polymers to the inner surface of the hollow fiber membrane, but also induces phase separation by acting as nuclei. This results in a hollow fiber membrane with a high hydrophilic polymer content on the inner surface and a high porosity.
[0107] When the surface in contact with the treatment solution is an inner surface, the core liquid temperature is preferably the same as or 5°C or more lower than the film-forming stock solution temperature, and more preferably 10°C or more lower.
[0108] The dew point temperature of the dry section has a significant impact, particularly on the outer surface of the hollow fiber membrane. However, controlling the dew point temperature allows for the control of the phase separation reaction of the film-forming solution. For example, moisture can be supplied to the outer surface of the hollow fiber membrane to form a dense layer. When the surface in contact with the liquid being treated is the inner surface, it is preferable that the humidity is regulated to a dew point of 20-40°C.
[0109] The length of the dry section determines the time from pore formation on the hollow fiber membrane surface to solidification, and is preferably between 10 and 250 mm. If the length of the dry section is 10 mm or more, the average pore diameter on the hollow fiber membrane surface becomes larger. On the other hand, if the length of the dry section is 250 mm or less, fiber movement is less likely to occur during the film formation process, and fiber breakage is less likely to occur.
[0110] A coagulation solution is a poor solvent for polysulfone polymers. Examples of coagulation solutions include alcohol, water, or glycerin, but water is preferred.
[0111] The coagulation bath temperature is preferably 30 to 100°C, and more preferably 60 to 90°C. The coagulation bath temperature greatly affects the average pore size on the surface of the hollow fiber membrane and the water permeability of the hollow fiber membrane. When the coagulation bath temperature is 30°C or higher, the pore size on the outer surface of the hollow fiber membrane increases, the permeable particle size increases, and water permeability improves. On the other hand, when the coagulation bath temperature is 100°C or lower, the porosity on the surface of the hollow fiber membrane decreases, and the strength of the hollow fiber membrane tends to improve.
[0112] In addition to the coagulation solution such as water, a good solvent for polysulfone polymers may be added to the coagulation bath in a ratio of 1 to 10% by mass. Adding a good solvent can mitigate the diffusion rate of the coagulation solution during desolvation, making it possible to create a suitable structure on the outer surface of the hollow fiber membrane. When the concentration of the good solvent is 1% by mass or more, it becomes easier to control the pore size and dense layer thickness on the outer surface of the hollow fiber membrane. On the other hand, when the concentration of the good solvent is 10% by mass or less, the desolvation of hydrophilic polymers is moderately promoted, making it easier to improve the strength of the hollow fiber membrane.
[0113] Hot water washing refers to immersing the hollow fiber membrane, after being immersed in a coagulation bath, in a hot water bath at 60°C or higher for at least one minute. Hot water washing removes excess solvent and hydrophilic polymers remaining on the hollow fiber membrane. If hydrophilic polymers have been added to the core solution, it is preferable to wind up the hollow fiber membrane after hot water washing, cut it into pieces of a certain length, and then perform additional hot water washing in order to effectively remove excess hydrophilic polymers and improve the water permeability of the hollow fiber membrane.
[0114] As a specific example, it is preferable to wind up the hollow fiber membrane after hot water washing, cut it into 400 mm lengths, wrap the resulting bundles in gauze, and then perform an additional hot water washing in hot water at 70°C or higher for 1 to 5 hours. By washing with hot water at 90°C or higher, excess hydrophilic polymers that are not supported or chemically immobilized on the hollow fiber membrane, as well as hydrophilic polymers that filled the pores on the surface of the hollow fiber membrane, will dissolve into the hot water and can be removed.
[0115] Although the hollow fiber membrane is in a wet state after the hot water washing described above, it is preferable to carry out a drying process from the viewpoint of further stabilizing the water permeability of the hollow fiber membrane. The temperature of the drying process is preferably 100°C or higher in order to evaporate the moisture. Furthermore, the temperature of the drying process is preferably 180°C or lower so as not to exceed the glass transition temperature of the polysulfone polymer.
[0116] In separation membranes used for biopharmaceutical purification, it is preferable to minimize the elution of hydrophilic polymers. To suppress the elution of hydrophilic polymers, it is preferable to crosslink the resulting hollow fiber membrane by heating and radiation.
[0117] In the heat crosslinking process, where the resulting hollow fiber membrane is heated, hydrophilic polymers present in the membrane are crosslinked. Since decomposition reactions can be minimized while crosslinking hydrophilic polymers, the heat crosslinking temperature is preferably 120 to 250°C, and more preferably 130 to 200°C. The heat crosslinking time is preferably 1 to 10 hours, and more preferably 3 to 8 hours.
[0118] In radiation crosslinking, where the resulting hollow fiber membrane is irradiated with radiation, hydrophilic polymers or the aforementioned polymer compound C are crosslinked with polysulfone-based polymers. Since the crosslinking reaction can be promoted while decomposition reactions are less likely to occur, the irradiation dose for radiation crosslinking is preferably 5 to 75 kGy, and more preferably 10 to 50 kGy. As the radiation to be irradiated, alpha rays, beta rays, gamma rays, X-rays, ultraviolet rays, or electron beams can be used.
[0119] When polymer compound C is supported, radiation is irradiated either with the hollow fiber membrane in the separation membrane module in contact with a solution containing polymer compound C, or with the solution removed from the separation membrane module after polymer compound C has been introduced to the surface, or with the hollow fiber membrane dried. This method is preferable because it achieves both the immobilization of polymer compound C and the sterilization of the separation membrane module. For sterilization, a certain degree of material penetration of the radiation is preferable, so among the above types of radiation, beta rays, gamma rays, X-rays, and electron beams are more preferable.
[0120] Furthermore, if the water content of the separation membrane is low during radiation irradiation, radiation-induced crosslinking reactions between hydrophobic and hydrophilic polymers become less likely to occur, resulting in a higher amount of eluted material. Therefore, the water content of the separation membrane during radiation irradiation is preferably between 1 and 350% by mass.
[0121] Polymer compound C, which has an ester group, readily generates radicals when irradiated with radiation, and therefore readily undergoes crosslinking reactions with the separation membrane material even under conditions of low water content and low radical generation due to water. For this reason, from the viewpoint of crosslinking polymer compound C, the water content in the separation membrane during radiation irradiation is preferably 1 to 50% by mass.
[0122] Furthermore, to facilitate crosslinking by radiation irradiation when the moisture content is low, it is preferable to use degassed water or to purge the inside of the separation membrane module with nitrogen when irradiating the separation membrane module with radiation.
[0123] Furthermore, antioxidants may be used to suppress the crosslinking reaction of polymer compound C caused by radiation irradiation. Antioxidants are substances that readily donate electrons to other molecules. Examples of antioxidants include, but are not limited to, water-soluble vitamins such as vitamin C, polyphenols, or alcoholic solvents such as methanol, ethanol, or propanol. These antioxidants may be used alone or in mixtures of two or more. When safety needs to be considered, antioxidants with low toxicity, such as ethanol or propanol, are preferably used.
[0124] <Separation Membrane Module> From the viewpoint of ease of use, the separation membrane of the present invention is preferably housed in a module case for use. That is, it is preferable that the separation membrane module contains the separation membrane of the present invention.
[0125] When the separation membrane of the present invention is a hollow fiber membrane, methods for modularizing the hollow fiber membrane include fixing it to a case while centrifuging, filling a case with hollow fiber membranes and then pouring potting material into both ends of the case to fix them in place, and shaping the hollow fiber membrane into a U-shape and fixing only the opening side of the hollow fiber membrane to the case.
[0126] An example of a method for modularizing hollow fiber membranes is as follows: First, the hollow fiber membranes are cut to the required length, bundled together in the required number, and placed in a cylindrical case. Then, temporary caps are placed on both ends, and potting material is added to both ends of the hollow fiber membranes. When adding the potting material, it is preferable to rotate the case with a centrifuge while adding the potting material, as this allows for uniform filling. However, it is also preferable to simply pour the potting material into the case with the caps positioned vertically downwards and then leave it to set. After the potting material has solidified, both ends of the hollow fiber membranes are cut so that both ends are open. Processing liquid inlet ports (hereinafter referred to as "headers") are attached to both ends of the case, and the headers and the nozzle portions of the case are plugged to obtain a hollow fiber membrane module.
[0127] It is preferable that the hollow fiber membrane is crimped in order to prevent the accumulation of the liquid being treated (such as culture medium for microorganisms or cells) within the hollow fiber membrane module. In other words, it is preferable that the hollow fiber membrane module contains the hollow fiber membrane of the present invention which has been crimped.
[0128] The effective membrane area of the hollow fiber membrane module should be appropriately selected according to the volume of liquid to be treated. Setting an unnecessarily large effective membrane area will result in a larger hollow fiber membrane module, making handling more complicated and increasing costs; therefore, it is preferable to set an appropriate effective membrane area. An effective membrane area of 0.01 m² is recommended. 2 Above, 12.0m 2 The following is preferable. From the viewpoint of processing capacity relative to the volume of liquid to be processed in general biopharmaceutical manufacturing, the effective membrane area is 0.02 m². 2 The above is more preferable, 0.05m 2 The above is even more preferable, 0.1m 2 The above is particularly preferable. On the other hand, since the module size can be reduced and handling is easy, the effective film area is 11.0 m². 2 The following is more preferable: 7.0m 2 The following is even more preferable: 5.0m 2 The following are particularly preferable.
[0129] There are no particular restrictions on the dimensions of the hollow fiber membrane module, but in order to achieve the preferred effective membrane area range and ease of handling of the module, the inner diameter is preferably 0.5 cm or more and 32.0 cm or less, more preferably 1.0 cm or more and 26.0 cm or less, and even more preferably 1.5 cm or more and 16.0 cm or less.
[0130] Furthermore, from the viewpoint of ease of handling the module, the effective length of the hollow fiber membrane inside the hollow fiber membrane module is preferably 5.0 cm or more, more preferably 10.0 cm or more, and even more preferably 15.0 cm or more. Also, since excessively long modules result in increased pressure loss during filtration, the module length is preferably 80.0 cm or less, more preferably 70.0 cm or less, and even more preferably 60.0 cm or less.
[0131] Furthermore, the ratio of the volume of the hollow fiber membrane to the volume inside the module, i.e., the packing rate, is preferably 30% or more and 70% or less, more preferably 35% or more and 65% or less, even more preferably 40% or more and 60% or less, and particularly preferably 45% or more and 55% or less, from the viewpoint of the ease of flow of the liquid to be treated inside the module and the effective use of the module volume.
[0132] The filling rate (%) can be calculated using the following formula 1. (Filling efficiency) = (Cross-sectional area of hollow fiber membrane) × (Number of hollow fiber membranes) / (Module cross-sectional area) × 100 ... Equation 1 The cross-sectional area of the hollow fiber membrane in Equation 1 is calculated using Equation 2 below, and the module cross-sectional area is calculated using Equation 3 below. Note that π is the ratio of a circle's circumference to its diameter (pi). (Cross-sectional area of hollow fiber membrane) = {(Outer diameter of hollow fiber membrane) / 2} 2 ×π...Equation 2 (Module cross-sectional area) = {(Module inner diameter) / 2} 2 ×π...Equation 3
[0133] In the separation membrane module of the present invention, from the viewpoint of suppressing bacterial growth during storage and suppressing freezing of the separation membrane, the water content in the separation membrane within the separation membrane module is preferably 1 to 350% by mass.
[0134] Furthermore, from the viewpoint of improving handling by reducing the weight of the separation membrane module, the water content of the separation membrane within the separation membrane module is preferably 1 to 50% by mass.
[0135] The separation membrane module of the present invention can be suitably used for the purification of microbial or cell-derived substances. The water permeability of the separation membrane module is 10 mL / Pa / h / m 2 Above, 300mL / Pa / h / m 2 The following is preferable: Higher water permeability can increase productivity, therefore the water permeability of the separation membrane module should be 20 mL / Pa / h / m². 2 The above is more preferable: 30 mL / Pa / h / m 2 The above is even more preferable. The upper limit is 250 mL / Pa / h / m 2 The following is more preferable: 200 mL / Pa / h / m² 2 The following are even more preferable.
[0136] As described above, the hollow fiber membrane module of the present invention may be a U-shaped module. That is, a U-shaped hollow fiber membrane module containing the hollow fiber membrane of the present invention is one preferred embodiment. A U-shaped module is a module in which the hollow fiber membrane of the present invention is folded back into a U shape, both ends of the hollow fiber membrane bundle are bonded to a case with resin, and both ends of the hollow fiber membrane are open. The U-shaped module is easy to handle and is suitable for research, testing, and inspection applications.
[0137] <Filtration device> To effectively utilize the separation membrane module of the present invention, it is preferable to use a filtration device that includes the separation membrane module and a liquid transfer pump. The type of liquid transfer pump used in the filtration device of the present invention is not particularly limited, but examples include peristaltic pumps, diaphragm pumps, syringe pumps, etc.
[0138] <Microorganisms, cell-derived substances, or purified products thereof> The separation membrane of the present invention is suitably used for the purification of microorganisms or cell-derived substances. Microorganisms or cell-derived substances that exhibit useful effects when administered to humans or animals are specifically called "biopharmaceuticals." That is, it is preferable to obtain microorganisms, cell-derived substances, or purified products thereof by filtering the culture medium or culture supernatant of microorganisms or cells with the separation membrane module of the present invention.
[0139] Examples of microorganisms or cell-derived substances include protein pharmaceuticals (hormones, enzymes, etc.), vaccines, vectors (gene therapy drugs), antibodies (immunoglobulins), and extracellular vesicles. However, because the separation membrane of the present invention has high permeability, it is preferably used for the purification of relatively large vectors, antibodies, or extracellular vesicles. In other words, it is preferable that the purified product of the above-mentioned microorganisms or cell-derived substances contains at least one of the vector, antibody, or extracellular vesicle. [Examples]
[0140] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0141] (1) Measurement of the thickness of the separation membrane When the separation membrane to be measured was flat, 16 randomly selected cross-sections of the separation membrane were measured using a 1000x lens on a microwatcher (VH-Z100; KEYENCE Corporation), and the average value was calculated.
[0142] When the separation membrane was in the form of a hollow fiber membrane, the inner diameter and film thickness of the hollow fiber membrane were measured by the following method. Specifically, the film thickness of 16 randomly selected hollow fiber membranes was measured using a 1000x lens of a microwatcher, and the average value a of the film thickness was calculated. The inner diameter of the hollow fiber membrane was calculated using the following formula 4. The outer diameter of the hollow fiber membrane was obtained by measuring the outer diameter of 16 randomly selected hollow fiber membranes using a laser displacement meter (e.g., LS5040T; KEYENCE Corporation), and the average value was used. Inner diameter of hollow fiber membrane (μm) = Average value of outer diameter of hollow fiber membrane - (2 × Average value of film thickness a) ... Equation 4
[0143] (2) Fabrication of hollow fiber membrane modules Three hollow fiber membranes were packed into a case approximately 5 mm in diameter and 17 cm in length. After potting both ends with Konishi Corporation's epoxy resin-based chemical reaction adhesive "Quick Mender" (registered trademark), the ends were cut to create an opening, thereby fabricating a hollow fiber membrane module with an effective length of 12 cm.
[0144] (3) Measurement of water permeability of hollow fiber membranes The hollow fiber membrane and the inside of the hollow fiber membrane module prepared by the method described in (2) above were washed with distilled water for 30 minutes. A water pressure of 20 kPa was applied to the inside of the hollow fiber membrane, and the amount of filtration per unit time that flowed out to the outside of the hollow fiber membrane was measured. The water permeability (UFR) was calculated using the following formula 5, and the value rounded to the first decimal place was used as the measurement data. UFR (mL / kPa / h / m) 2 ) = Qw / (P×T×A) ...Equation 5 The parameters in Equation 5 are as follows: Qw: Filtration volume (mL), T: Flow time (h), P: Pressure (kPa), A: Inner surface area of hollow fiber membrane (m²) 2 )
[0145] The inner surface area A of the hollow fiber membrane was determined by multiplying the inner diameter of the hollow fiber by pi (π) and the length of the portion of the hollow fiber used for measuring water permeability that was effective for measurement.
[0146] (4) Measurement of particle transmittance The particle transmittance of the separation membrane was measured using commercially available polystyrene latex beads (hereinafter referred to as "LB") with an average particle size of 0.06 μm (Thermo Fisher's "Sulfate Latex Beads"). The relationship between the concentration of the LB suspension and its turbidity was calculated beforehand from the absorbance at a wavelength of 260 nm measured by ultraviolet-visible spectroscopy. The turbidity of the filtrate filtered through the separation membrane was measured, and the particle transmittance was determined using the following formula 6. The liquid to be treated was LB diluted to a concentration of 0.02% by mass (200 ppm) with pure water.
[0147] For the measurement, two hollow fiber modules were prepared, and treated water was flowed from the inside to the outside of the separation membrane at a pressure of 14 kPa. The average value for n=2 was calculated, and the value was rounded to the first decimal place to obtain the measurement data. Particle transmittance (%) = {(Turbidity of filtrate) / (Turbidity before treatment)} × 100 ... Equation 6
[0148] (5) Measurement of the depth of the dense layer The separation membrane was prepared by wetting it with water for 5 minutes, then freezing it with liquid nitrogen, quickly folding it, and freeze-drying it. The resulting membrane was used as the measurement sample. The cross-section of the separation membrane was observed at a magnification of 5000x using a SEM (S-5500, Hitachi High-Technologies Corporation), and the image was imported into a computer in TIFF format. The size of the imported image was 1280 pixels x 960 pixels. If the pores in the cross-section were blocked upon observation with the SEM, the sample preparation was repeated. Pore blockage may occur when the separation membrane deforms in the direction of stress during the cutting process.
[0149] The entire film thickness was observed at an arbitrary magnification to identify the region with the smallest pore size. Next, an SEM image was acquired so that the region with the smallest pore size and the surface closest to it were included in the observation area. If the entire observation area could not be contained within the observation magnification (5000x), two or more SEM images were combined.
[0150] The obtained SEM images were analyzed using image processing software (ImageJ (version 1.52), developed by the National Institutes of Health, USA). A threshold was set for binarization so that the structured parts were represented as bright and the rest as dark, resulting in an image where the bright parts were white and the dark parts were black. If the structured parts and the rest could not be separated by the difference in contrast within the image, the image was cut at points with the same contrast, each section was binarized, and then the original images were stitched back together.
[0151] If two holes were observed in the depth direction, the shallower hole was measured. If part of a hole was outside the measurement range, that hole was excluded. The images contained noise, and dark areas with five or fewer consecutive pixels were treated as bright areas, i.e., structural parts, because it was impossible to distinguish between noise and holes.
[0152] The number of pixels in the scale bar, which indicates a known length within the image, was measured, and the length per pixel was calculated. The number of pixels in the detected holes was measured, and the hole area was calculated by multiplying the number of pixels in the holes by the square of the length per pixel.
[0153] The diameter of the circle corresponding to the pore area was calculated using Equation 7 below and defined as the pore diameter. The pore area corresponding to a pore diameter of 0.5 μm is 0.2 μm. 2 That is the case. Pore diameter (μm)=2×(pore area / π) 1 / 2 ...Formula 7
[0154] In the binarized image, pores with a diameter of 0.5 μm or more, i.e., pores with a pore area of 0.2 μm 2Identify the pores that meet the above criteria, draw perpendicular lines from one surface of the separation membrane to the other surface (from the outer surface to the inner surface in the case of a hollow fiber membrane), and among them, determine the pore area of 0.2 μm². 2 Among the layers where no pores exceeding the specified threshold were observed, the thickest region was defined as the dense layer, and the distance from the surface closest to the dense layer to its edge was measured. Three measurements were taken within the same image. The same measurements were then performed on 10 more images, and the average value of these 30 measurement data points was calculated. The value was rounded to two decimal places and defined as the thickness of the dense layer.
[0155] (6) Average pore size of the surface of the separation membrane The separation membrane was wetted in water for 5 minutes, then frozen with liquid nitrogen, and freeze-dried before being used as the measurement sample. If the separation membrane was a hollow fiber membrane, it was cut into a semi-cylindrical shape, exposing the inner surface. The surface of the separation membrane was observed at 2000x magnification using a scanning electron microscope (SEM) (S-5500, Hitachi High-Technologies Corporation), and the image was imported into a computer in TIFF format. The size of the imported image was 1280 pixels × 960 pixels. The number of pores and the area of each pore were measured for a 40 μm × 40 μm area on the separation membrane surface using image processing software (ImageJ (version 1.52), developed by the National Institutes of Health, USA). The measurement of the 40 μm × 40 μm area was repeated until the total number of measured pores exceeded 50, and data was added.
[0156] If two holes were observed in the depth direction, the exposed portion of the deeper hole was measured. If part of the hole was outside the measurement range (field of view of the SEM image), that hole was excluded. The SEM images were binarized to obtain an image in which the void area was black and the structure area was white. If the difference in contrast within the analyzed image made it impossible to clearly binarize the void area and the structure area, the void area was blacked out before image processing, the hole was fitted into a circular shape, and the hole diameter was measured.
[0157] The average pore size was calculated from the measurement results using the following formula 8, and rounded to the third decimal place. Average pore diameter (μm)={(S / a) / π} 1 / 2 ×2...Formula 8 The parameters in Equation 8 are as follows: a: Number of holes measured, S: Sum of the areas of the measured holes (μm²) 2 ), π: Pi
[0158] (7) X-ray photoelectron spectroscopy (XPS) measurement For each example and comparative example, if the separation membrane to be measured was in the form of a flat membrane, one side and the other side were measured as is. If the separation membrane was in the form of a hollow fiber membrane, it was cut into a semi-cylindrical shape with a single blade, and the inner or outer surface of the hollow fiber membrane was measured. The separation membranes were rinsed with ultrapure water and dried at room temperature at 0.5 Torr for 10 hours before being used as measurement samples. The measurement apparatus and conditions are as follows.
[0159] Measurement device: Quantera SXM (manufactured by Ulvac-PHI) Excitation X-rays: monochromatic Al K α1、α2 Line (1486.6eV) X-ray diameter: 100 μm Photoelectron escape angle: 45° (detector tilt relative to the sample surface).
[0160] From the obtained photoelectron spectra, the presence or absence of ester groups (COO) in the separation membrane, and if present, their abundance, were determined by analysis. 1s The peak is mainly CH x CS, CC and C=C-derived components, mainly CO and CN-derived components, π-π * Since it consists of five components: components derived from satellites, components derived from C=O, and components derived from COO, the peaks were split into five components.
[0161] The ingredients derived from COO are mainly CH xThe peaks appearing from +4.0 to 4.2 eV above the main peaks (around 285 eV) originating from CS, CC, and C=C were used. The atomic abundance (atomic %) was calculated from the area ratio and rounded to the second decimal place. If the ratio of the peak area originating from the ester group to the total peak area originating from carbon was 0.4% or less as a result of peak splitting, it was judged to be noise and the ester group was considered absent (below the detection limit). The measurement was performed at two different locations on the separation membrane, and the average value of the values from these two locations was used.
[0162] (8) TOF-SIMS measurement The separation membranes obtained in each example and comparative example were wetted by immersing them in pure water for 5 minutes, and then cut into lengths of approximately 1 cm or less using a single-edged blade or the like. The wet separation membranes were rapidly frozen to form sample blocks. The sample blocks were mounted in an ultramicrotome with a cryosystem, and thin sections were made at a temperature of -65°C with a thickness of 250 nm or 1 μm (if the pore size of the sample separation membrane was large and brittle). These sections were then mounted on a glass slide or an ITO-coated glass substrate to form the measurement samples. The measurement samples were dried at room temperature and atmospheric pressure for 10 hours before being subjected to measurement. The measurement equipment and conditions are as follows.
[0163] Measurement device: TOF.SIMS 5 (manufactured by ION-TOF) Primary ion: Bi3 ++ Primary ion acceleration voltage: 30kV Pulse width: 117.6 ns Secondary ion polarity: Positive only Number of scans: 256 scans Raster size: 120 x 150 μm Mass range (m / z): 0~1,500
[0164] From the obtained mass m / z spectra, the ion signal intensity originating from the ester group of polymer compound C in the separation membrane was analyzed. However, if the carboxylic acid ion intensity relative to the total secondary ion detection intensity was 0.1% or less, it was considered noise, and the absence of carboxylic acid was assumed (below the detection limit). For the separation membrane, a secondary ion profile was obtained in the direction of the membrane cross-section when the separation membrane was flat, and for the hollow fiber membrane, a secondary ion profile was obtained in the direction perpendicular to the tangent to the inner surface of the hollow fiber membrane in the cross-sectional view.
[0165] In the obtained secondary ion detection profile, the average ion detection intensity in a 20 μm region was calculated from both the one surface and the other surface (outer surface and inner surface in the case of a hollow fiber membrane), and the ratio of the average value on the surface closer to the dense layer to the average value on the surface further away from the dense layer was determined. Similar measurements were performed on three different cross-sections of each separation membrane, and the average of the ratios of the average values was calculated and rounded to two decimal places.
[0166] (9) Measurement of nitrogen content in the separation membrane The separation membranes obtained in each example and comparative example were dried under reduced pressure at 60°C for 3 hours to prepare the measurement samples. The measurement apparatus and conditions for each separation membrane sample are as follows. Measurements were performed three times, and the average value was rounded to the first decimal place to obtain the measured value.
[0167] Measurement device: Trace nitrogen analyzer ND-100 (manufactured by Mitsubishi Chemical Corporation) Electric furnace temperature (horizontal reactor) Pyrolysis part: 800℃ Catalyst part: 900℃ Main O2 flow rate: 300 mL / min Sub-O2 flow rate: 300 mL / min Ar flow rate: 400mL / min Sens.: Low
[0168] (10) Measurement of protein adsorption Gamma globulin (Sigma-Aldrich, derived from human blood, catalog number: G4386) was dissolved in phosphate-buffered saline (PBS(-)) to a concentration of 0.2 g / L. Separately, 0.1 g of a wet separation membrane was weighed, shredded into pieces approximately 1 mm to 2 mm in size, and 10 mL of the prepared gamma globulin solution (0.2 g / L) was added to it. The mixture was shaken using a thermomixer at 37°C for 4 hours. Subsequently, the solution was color-developed using the "Pierce® BCA Protein Assay Kit" (catalog number: 23225) from ThermoFisher Scientific, and the absorbance at a wavelength of 562 nm was measured. A calibration curve was created by preparing a 2-fold dilution series of gamma globulin solutions, color-developing them using the "Pierce® BCA Protein Assay Kit," and measuring the absorbance at a wavelength of 562 nm. The amount of γ-globulin adsorbed on the separation membrane surface was determined by converting it to the γ-globulin solution concentration using a calibration curve that was created.
[0169] (11) Measurement of water content in the separation membrane The mass of the separation membrane module after removing the rubber stopper following gamma-ray irradiation was defined as a: Mass of the separation membrane module before oven drying. Subsequently, the separation membrane module was placed in a vacuum dryer set to 50°C and dried at 0.5 Torr for 12 hours. The mass measured after drying was defined as b: Mass of the separation membrane module after oven drying. Furthermore, another module prepared in the same manner was disassembled, the separation membrane was removed, and the mass measured after vacuum drying at 50°C and 0.5 Torr for 12 hours was defined as c: Mass of the separation membrane after oven drying. The moisture content in the separation membrane was calculated using the following formula 9, and the measured value was rounded to two decimal places. Moisture content in separation membrane (mass%) = 100×(ab) / c...Equation 9 The parameters in Equation 9 are as follows: a: Mass of the separation membrane module before oven drying (g), b: Mass of the separation membrane module after oven drying (g), c: Mass of the separation membrane at the time of oven drying (g)
[0170] (Example 1) 15% by mass of polysulfone (SOLVAY's "Udel" (registered trademark) P-3500) and 7% by mass of polyvinylpyrrolidone (ASHLAND LCC's povidone (PLASDONE (registered trademark)) K90) were added to a solvent consisting of 75% by mass of N,N-dimethylacetamide and 3% by mass of water, and the mixture was heated at 90°C for 14 hours to dissolve and obtain a film-forming stock solution. This film-forming stock solution was dispensed from an orifice-type double-cylindrical nozzle with an outer diameter of 1.0 mm and an inner diameter of 0.7 mm, adjusted to 37°C. Simultaneously, a core solution consisting of 92% by mass of N,N-dimethylacetamide and 8% by mass of water was dispensed from the inner tube.
[0171] After passing through a 70 mm long dry section set to a dew point of 28°C, the material was immersed in an 80°C solidification bath filled with water to solidify. Further, it was washed with hot water in a 60°C bath and then wound onto a reel frame at a speed of 30 m / min to obtain a moist hollow fiber membrane. At this point, the inner diameter of the hollow fiber membrane was 295 μm and the film thickness was 80 μm.
[0172] The obtained wet hollow fiber membrane was cut into 0.4 m lengths and divided into smaller portions. After being immersed in a 90°C hot water bath for 3 hours for hot water washing, it was subjected to a heat crosslinking treatment at 170°C for 6 hours in a dry heat dryer to obtain hollow fiber membrane 1. Furthermore, separation membrane module 1A was prepared using the method described in (2) above and washed with distilled water for 30 minutes.
[0173] An aqueous solution of vinylpyrrolidone / vinyl propanoate random copolymer (molar fraction of vinyl propanoate units 40%, weight-average molecular weight 58,300) dissolved in ethanol at a concentration of 100 ppm and a concentration of 0.1% by mass was passed through the hollow fiber membrane module 1A at a flow rate of 0.56 mL / min, and then 2.8 mL was passed through the hollow fiber membrane from the inside to the outside, thereby adhering the vinylpyrrolidone / vinyl propanoate random copolymer to the entire membrane.
[0174] Next, 0.56 mL of pure water was passed through the hollow fiber membrane at a flow rate of 0.56 mL / min, and then 2.8 mL of pure water was passed from the inside to the outside of the hollow fiber membrane to wash away excess vinylpyrrolidone / vinyl propanoate random copolymer. Separation membrane module 1B was then obtained by irradiation with 25 kGy of gamma rays. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0175] In separation membrane module 1B, polymer compound A is polysulfone, polymer compound B is polyvinylpyrrolidone, and polymer compound C is vinylpyrrolidone / vinyl propanoate random copolymer.
[0176] (Example 2) 13% by mass of polysulfone (SOLVAY's "Udel" (registered trademark) P-3500) and 7% by mass of polyvinylpyrrolidone (ASHLAND LCC's povidone (PLASDONE (registered trademark)) K90) were added to a solvent consisting of 77% by mass of N,N-dimethylacetamide and 3% by mass of water, and the mixture was heated at 90°C for 14 hours to dissolve and obtain a film-forming stock solution. This film-forming stock solution was dispensed from an orifice-type double-cylindrical nozzle with an outer diameter of 1.4 mm and an inner diameter of 1.1 mm, adjusted to 37°C. Simultaneously, a core solution consisting of 92% by mass of N,N-dimethylacetamide and 8% by mass of water was dispensed from the inner tube.
[0177] After passing through a 70 mm long dry section set to a dew point of 28°C, the material was immersed in an 80°C solidification bath filled with water to solidify. Further, it was washed with hot water in a 60°C bath and then wound onto a reel frame at a speed of 30 m / min to obtain a wet hollow fiber membrane. At this point, the inner diameter of the hollow fiber membrane was 1033 μm and the film thickness was 155 μm.
[0178] The obtained wet hollow fiber membrane was cut into 0.4 m lengths and divided into smaller portions. After being immersed in a 90°C hot water bath for 3 hours for hot water washing, it was subjected to a heat crosslinking treatment at 170°C for 6 hours in a dry heat dryer to obtain hollow fiber membrane 2. Furthermore, separation membrane module 2A was prepared using the method described in (2) above and washed with distilled water for 30 minutes.
[0179] An aqueous solution of vinylpyrrolidone / vinyl propanoate random copolymer (molar fraction of vinyl propanoate units 40%, weight-average molecular weight 58,300) dissolved in ethanol at a concentration of 500 ppm and a concentration of 0.1% by mass was passed through the hollow fiber membrane module 2A at a flow rate of 2.2 mL / min, and then 11.0 mL was passed through the hollow fiber membrane from the inside to the outside, thereby adhering the vinylpyrrolidone / vinyl propanoate random copolymer to the entire membrane.
[0180] Next, 11.0 mL of pure water was passed through the hollow fiber membrane from the inside to the outside, and then 2.2 mL of pure water was passed through the inside of the hollow fiber membrane to wash away excess vinylpyrrolidone / vinyl propanoate random copolymer. Separation membrane module 2B was then obtained by irradiation with 25 kGy of gamma rays. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0181] In separation membrane module 2B, polymer compound A is polysulfone, polymer compound B is polyvinylpyrrolidone, and polymer compound C is vinylpyrrolidone / vinyl propanoate random copolymer.
[0182] (Example 3) In the hollow fiber membrane module 2A, obtained in the same manner as in Example 2, vinylpyrrolidone / vinyl propanoate random copolymer was attached to the entire membrane in the same manner as in Example 2, except that instead of an aqueous solution of vinylpyrrolidone / vinyl propanoate random copolymer (molar fraction of vinyl propanoate units 40%, weight-average molecular weight 58,300) dissolved in ethanol at a concentration of 500 ppm and a concentration of 0.1 mass%, an aqueous solution of vinylpyrrolidone / vinyl propanoate random copolymer dissolved in ethanol at a concentration of 1000 ppm and a concentration of 1 mass% was used. The membrane was then irradiated with gamma rays to obtain a separation membrane module 3B. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0183] In separation membrane module 3B, polymer compound A is polysulfone, polymer compound B is polyvinylpyrrolidone, and polymer compound C is vinylpyrrolidone / vinyl propanoate random copolymer.
[0184] (Comparative Example 1) Separation membrane module 1A, obtained by the same method as in Example 1, was washed with distilled water for 30 minutes, and then irradiated with 25 kGy of gamma rays to obtain hollow fiber membrane module 4B. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0185] In this case, in the separation membrane precursor within the hollow fiber membrane module 4B, polymer compound A is polysulfone and polymer compound B is polyvinylpyrrolidone, but polymer compound C is not present.
[0186] Since polymer compound C does not have a protein adsorption inhibitory effect, it can be seen that the amount of protein adsorbed is higher compared to the example.
[0187] (Comparative Example 2) 20% by mass of polysulfone (SOLVAY's "Udel" (registered trademark) P-3500), 6% by mass of polyvinylpyrrolidone (ASHLAND LCC's Povidone (PLASDONE) K29 / K32), and 3% by mass of polyvinylpyrrolidone (ASHLAND LCC's Povidone (PLASDONE) K90) were added to a solvent consisting of 70% by mass of N,N-dimethylacetamide and 1% by mass of water, and the mixture was heated at 90°C for 14 hours to dissolve and obtain a film-forming stock solution. This film-forming stock solution was discharged from an orifice-type double-cylindrical nozzle adjusted to 40°C, and simultaneously, a core solution consisting of 72% by mass of N,N-dimethylacetamide and 28% by mass of water was discharged from the inner tube.
[0188] After the discharged liquid was passed through a 350 mm long space in the dry section, it was guided into a 40°C solidification bath containing water to obtain a hollow fiber membrane 5 with an asymmetric structure having a dense layer on the inner surface and a coarse layer on the outer surface. The obtained hollow fiber membrane had an inner diameter of 280 μm and a film thickness of 50 μm. Furthermore, the separation membrane module 5A was prepared using the method described in (2) above, except that the number of hollow fiber membranes packed was changed from 3 to 10, and washed with distilled water for 30 minutes.
[0189] Instead of using the aqueous solution of vinylpyrrolidone / vinyl propanoate random copolymer at a concentration of 500 ppm and ethanol at a concentration of 0.1% by mass used in Example 2, an aqueous solution of vinylpyrrolidone / vinyl hexanoate random copolymer (molar fraction of vinyl hexanoate units 40%, weight-average molecular weight 2,200) at a concentration of 100 ppm and ethanol at a concentration of 0.1% by mass was used. 10 mL of the modified aqueous solution was passed through the hollow fiber membrane module 5A from the outside to the inside at an applied pressure of 100 kPa. This operation coated the membrane with vinylpyrrolidone / vinyl hexanoate random copolymer. Further irradiation with gamma rays was performed to obtain separation membrane module 5B. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0190] The XPS measurement results for Comparative Example 2, shown in Table 3, indicate that a large amount of vinylpyrrolidone / vinyl hexanoate random copolymer is present on the inner surface side of the membrane. Possible contributing factors include the fact that the liquid was passed through the hollow fiber membrane 5, which has a small surface pore size, from the outer surface side under high pressure, causing polymer compound C to be pressed against the dense layer on the inner surface, and that there was no process to wash away excess copolymer (polymer compound C).
[0191] (Example 4) 13% by mass of polysulfone (SOLVAY's "Udel" (registered trademark) P-3500) and 7% by mass of polyvinylpyrrolidone (ASHLAND LCC's povidone (PLASDONE (registered trademark)) K90) were added to a solvent consisting of 77% by mass of N,N-dimethylacetamide and 3% by mass of water, and the mixture was heated at 90°C for 14 hours to dissolve and obtain a film-forming stock solution. This film-forming stock solution was dispensed from an orifice-type double-cylindrical nozzle with an outer diameter of 1.8 mm and an inner diameter of 1.4 mm, adjusted to 37°C. Simultaneously, a core solution consisting of 92% by mass of N,N-dimethylacetamide and 8% by mass of water was dispensed from the inner tube.
[0192] After passing through a 70 mm long dry section set to a dew point of 28°C, the material was immersed in an 80°C solidification bath filled with water to solidify. Further, it was washed with hot water in a 60°C bath and then wound onto a reel frame at a speed of 30 m / min to obtain a moist hollow fiber membrane. At this point, the inner diameter of the hollow fiber membrane was 1360 μm and the film thickness was 170 μm.
[0193] The obtained wet hollow fiber membrane was cut into 0.4 m lengths and divided into smaller portions. After being immersed in a 90°C hot water bath for 3 hours for hot water washing, it was subjected to a heat crosslinking treatment at 170°C for 6 hours in a dry heat dryer to obtain hollow fiber membrane 6. Furthermore, a separation membrane module 6A was prepared using the method described in (2) above and washed with distilled water for 30 minutes.
[0194] An aqueous solution of vinylpyrrolidone / vinyl propanoate random copolymer (molar fraction of vinyl propanoate units 40%, weight-average molecular weight 58,300) dissolved in ethanol at a concentration of 500 ppm and a concentration of 0.1% by mass was passed through the hollow fiber membrane module 6A at a flow rate of 3.8 mL / min, and then 19.0 mL was passed through the hollow fiber membrane from the inside to the outside, thereby adhering the vinylpyrrolidone / vinyl propanoate random copolymer to the entire membrane.
[0195] Next, 19.0 mL of pure water was passed through the hollow fiber membrane from the inside to the outside, and then 3.8 mL of pure water was passed through the inside of the hollow fiber membrane to wash away excess vinylpyrrolidone / vinyl propanoate random copolymer. Furthermore, 25 kGy of gamma rays was irradiated to obtain separation membrane module 6B. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0196] In separation membrane module 6B, polymer compound A is polysulfone, polymer compound B is polyvinylpyrrolidone, and polymer compound C is vinylpyrrolidone / vinyl propanoate random copolymer.
[0197] (Example 5) 13% by mass of polysulfone (SOLVAY's "Udel" (registered trademark) P-3500) and 7% by mass of polyvinylpyrrolidone (ASHLAND LCC's povidone (PLASDONE (registered trademark)) K90) were added to a solvent consisting of 77% by mass of N,N-dimethylacetamide and 3% by mass of water, and the mixture was heated at 90°C for 14 hours to dissolve and obtain a film-forming stock solution. This film-forming stock solution was dispensed from an orifice-type double-cylindrical nozzle with an outer diameter of 1.9 mm and an inner diameter of 1.4 mm, adjusted to 37°C. Simultaneously, a core solution consisting of 92% by mass of N,N-dimethylacetamide and 8% by mass of water was dispensed from the inner tube.
[0198] After passing through a 70 mm long dry section set to a dew point of 28°C, the material was immersed in an 80°C solidification bath filled with water to solidify. Further, it was washed with hot water in a 60°C bath and then wound onto a reel frame at a speed of 30 m / min to obtain a moist hollow fiber membrane. At this point, the inner diameter of the hollow fiber membrane was 1515 μm and the film thickness was 180 μm.
[0199] The obtained wet hollow fiber membrane was cut into 0.4 m lengths and divided into smaller portions. After being immersed in a 90°C hot water bath for 3 hours for hot water washing, it was subjected to a heat crosslinking treatment at 170°C for 6 hours in a dry heat dryer to obtain hollow fiber membrane 7. Furthermore, a separation membrane module 7A was prepared using the method described in (2) above and washed with distilled water for 30 minutes.
[0200] An aqueous solution of vinylpyrrolidone / vinyl propanoate random copolymer (molar fraction of vinyl propanoate units 40%, weight-average molecular weight 58,300) dissolved in ethanol at a concentration of 500 ppm and a concentration of 0.1% by mass was passed through the hollow fiber membrane module 7A at a flow rate of 4.7 mL / min. Then, 23.5 mL of the solution was passed from the inside to the outside of the hollow fiber membrane, thereby adhering the vinylpyrrolidone / vinyl propanoate random copolymer to the entire membrane.
[0201] Next, 23.5 mL of pure water was passed through the hollow fiber membrane from the inside to the outside, and then 4.7 mL of pure water was passed through the inside of the hollow fiber membrane to wash away excess vinylpyrrolidone / vinyl propanoate random copolymer. Furthermore, 25 kGy of gamma rays was irradiated to obtain separation membrane module 7B. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0202] In separation membrane module 7B, polymer compound A is polysulfone, polymer compound B is polyvinylpyrrolidone, and polymer compound C is vinylpyrrolidone / vinyl propanoate random copolymer.
[0203] (Example 6) In the hollow fiber membrane module 2A obtained by the same method as in Example 2, 2.2 mL of an aqueous solution prepared by dissolving vinylpyrrolidone / vinyl propanoate random copolymer (molar fraction of vinyl propanoate units 40%, weight-average molecular weight 58,300) at a concentration of 500 ppm and ethanol at a concentration of 0.1 mass% was passed through the inside of the hollow fiber membrane at a flow rate of 2.2 mL / min. Then, 11.0 mL was passed through the hollow fiber membrane from the inside to the outside, so that the vinylpyrrolidone / vinyl propanoate random copolymer adhered to the entire membrane. Compressed air at 50 kPa was flowed through the outside and inside of the hollow fiber membrane for 20 seconds each, so that only the hollow fiber membrane was wet. Furthermore, after purging the inside of the hollow fiber membrane module 2A with nitrogen, it was capped with an oxygen-impermeable rubber stopper, and irradiated with 25 kGy of gamma rays to obtain separation membrane module 8B. The data obtained from the measurements in (3) to (11) above are shown in Tables 1 to 3.
[0204] The oxygen concentration inside the hollow fiber membrane module 2A immediately before capping with a rubber stopper was less than 1%. In the separation membrane module 8B, polymer compound A is polysulfone, polymer compound B is polyvinylpyrrolidone, and polymer compound C is vinylpyrrolidone / vinyl propanoate random copolymer.
[0205] [Table 1]
[0206] [Table 2]
[0207] [Table 3] [Industrial applicability]
[0208] The separation membrane of the present invention may be particularly useful in the perfusion culture process in antibody drug production. The perfusion culture process involves gradually withdrawing the culture medium containing antibodies from the culture vessel and sending it to the downstream purification process. If filtration in the perfusion culture process can be sustained for a long period of time, it is expected that the series of downstream purification processes can be operated continuously, and antibodies that have undergone the final purification process can be continuously obtained over a long period of time. [Explanation of Symbols]
[0209] Surface on the side closer to the dense layer...1, Throat representing the interconnected structure...2
Claims
1. It contains polymer compound A as the main component, hydrophilic polymer compound B and polymer compound C having an ester group, and has a dense layer. A separation membrane for purifying microbial or cell-derived substances that satisfies the following conditions (A) to (C). (A) When the surfaces on both sides of the separation membrane are measured by X-ray photoelectron spectroscopy (XPS), the peak area derived from the ester group carbon atoms of polymer compound C among the total carbon-derived peak area is 0.5 atomic% or more and 10.0 atomic% or less. (B) When the surfaces on both sides of the separation membrane are measured by X-ray photoelectron spectroscopy (XPS), the ratio of the atomic abundance of the surface on the side with a larger peak area derived from ester group carbon atoms to the atomic abundance of the surface on the side with a smaller peak area derived from ester group carbon atoms is 1.0 or more and 2.2 or less. (C) In time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis of the cross-section of the separation membrane in the thickness direction, the average detection intensity of ions derived from the ester group of polymer compound C in the region 20 μm from the surface on the side closer to the dense layer is 1.1 times or more and 10.0 times or less than the average detection intensity in the region 20 μm from the surface on the side farther from the dense layer.
2. The separation membrane according to claim 1, wherein, in time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis of the film thickness cross-section, the average detection intensity of ions derived from the ester group of polymer compound C is 0.01 times or more and 1.50 times or less than the average detection intensity of ions derived from polymer compound B in a region 20 μm from any surface.
3. The separation membrane according to claim 1 or 2, wherein the average pore size of the surface on the side closest to the dense layer is 0.04 μm or more and 2.00 μm or less.
4. The separation membrane according to claim 1 or 2, wherein, in a cross-section in the film thickness direction, the porosity in the region from the surface on the side closest to the dense layer to a depth of 20 μm is 25% or more and 75% or less.
5. The separation membrane according to claim 1 or 2, wherein in a cross-section of the separation membrane in the thickness direction, the dense layer is located at a depth of 1 μm or more and 20 μm or less from the surface.
6. The separation membrane according to claim 1 or 2, wherein the separation membrane is a hollow fiber membrane.
7. The separation membrane according to claim 1 or 2, wherein the polymer compound A is a polysulfone-based polymer compound.
8. The separation membrane according to claim 1 or 2, wherein the polymer compound B is a polymer compound containing nitrogen atoms.
9. The separation membrane according to claim 1 or 2, wherein the polymer compound C is a polymer compound having a monocarboxylate vinyl ester unit as a repeating unit.
10. A separation membrane according to claim 1 or 2, wherein the nitrogen content is 2.0 mg / g or more and 5.0 mg / g or less.
11. A separation membrane according to claim 1 or 2, wherein the film thickness is 60 μm or more and 200 μm or less.
12. The separation membrane according to claim 1 or 2, wherein the transmittance of particles with a particle size of 0.06 μm is 1% or more and 100% or less.
13. A separation membrane module containing the separation membrane according to claim 1 or 2.
14. The separation membrane module according to claim 13, wherein the water content in the separation membrane is 1 to 350% by mass.
15. The separation membrane module according to claim 14, wherein the water content in the separation membrane is 1 to 50% by mass.
16. A filtration apparatus comprising a separation membrane module and a liquid transfer pump as described in claim 13.
17. A purified product of microbial or cell-derived substances obtained by filtering a culture medium or culture supernatant of a microorganism or cell using the separation membrane module described in claim 13.
18. The purified product according to claim 17, wherein the product produced from the microorganism or cell is a vector, an antibody, or an extracellular vesicle.
Citation Information
Patent Citations
Fire warning device
JP1990018695A
Polysulfone semipermeable membrane and its production
JP1994238139A
Separation membrane, method of producing the same and separation membrane module using the separation membrane
WO2009123088A1
Porous separation membrane
WO2021100804A1